2011
DOI: 10.1155/2011/396982
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Phylogeography of the Coral Triangle and Implications for Marine Management

Abstract: Extreme concentration of marine biodiversity and exploitation of marine resources in the Coral Triangle pose challenges to biogeographers and resource managers. Comparative phylogeography provides a powerful tool to test biogeographic hypotheses evoked to explain species richness in the Coral Triangle. It can also be used to delineate management units for marine resources. After about a decade of phylogeographical studies, patterns for the Coral Triangle are emerging. Broad connectivity in some species support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
212
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(233 citation statements)
references
References 138 publications
(241 reference statements)
13
212
0
1
Order By: Relevance
“…These cases illustrate the extreme diversity in outcomes that is expected from a group of organisms spread across 500 million years of evolutionary history. However, recent studies that compare many species across the same range have found congruent genetic partitions , Carpenter et al 2011. These studies also reveal extensive gaps in comparative studies of plants, prokaryotes, pelagic organisms, oceanic migrants, marine birds, and marine mammals.…”
Section: The Comparative Advantagementioning
confidence: 97%
See 1 more Smart Citation
“…These cases illustrate the extreme diversity in outcomes that is expected from a group of organisms spread across 500 million years of evolutionary history. However, recent studies that compare many species across the same range have found congruent genetic partitions , Carpenter et al 2011. These studies also reveal extensive gaps in comparative studies of plants, prokaryotes, pelagic organisms, oceanic migrants, marine birds, and marine mammals.…”
Section: The Comparative Advantagementioning
confidence: 97%
“…Furthermore, species of greater interest for management and conservation may be subject to tightly-focused studies. However, where possible, the comparisons of multiple co-distributed species are desirable to flesh out biogeographic history (Carpenter et al 2011. For example, congruent phylogeographic breaks among multiple species may indicate a shared history, especially when found at the boundaries of biogeographic provinces (Avise 1992, Dawson 2001, 2011 see Table 1).…”
Section: The Comparative Advantagementioning
confidence: 99%
“…The area covered includes Santini & Winterbottom (2002) areas 9-11, or Spalding et al (2007) ecoregions 9, 25, 26, 28 and 30. This large region has some coincident phylogeographic breaks (Carpenter et al 2011) in the Coral Triangle region, although the northwestern boundaries are more difficult to define (Briggs & Bowen 2012). We prepared this checklist because we have begun to study some polychaete families from the Philippine region (Williams & Gosliner 2014), and in anticipation of the many undescribed species that are being or will be discovered soon (Al-Hakim & Glasby 2004.…”
Section: Introductionmentioning
confidence: 99%
“…The Indo-Pacific Ocean is a biodiversity hotspot for marine organisms (Carpenter et al, 2011). The discontinuity produced by the many islands in the region is important, in that it provides both habitat complexity and potentially isolated populations, leading to a rich diversity of marine life (Briggs, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The discontinuity produced by the many islands in the region is important, in that it provides both habitat complexity and potentially isolated populations, leading to a rich diversity of marine life (Briggs, 2000). In this area, research has mostly focused on marine animals (Briggs, 2005;Reaka et al, 2008;Carpenter et al, 2011;Mirams et al, 2011), rather than macroalgae. Benthic macroalgae are important primary producers in these coastal environments and structure ecological communities.…”
Section: Introductionmentioning
confidence: 99%